The Relationship Between Nutritional Status and Quality of Life Patient Disease Kidney Chronic Undergoing Hemodialysis - Abu Bakar; Rini Purwanti; Desak Putu Kuniawati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2025)
The prevalence of Protein Energy Malnutrition is reported to vary between 10% and 36% of all patients undergoing hemodialysis. Patients with chronic kidney failure undergoing hemodialysis need good nutritional status to improve their health. This situation requires a deeper analysis of important chronic kidney disease nutrition aimed at improving quality of life. This study aimed to analyze the relationship between nutritional status and quality of life of chronic kidney disease patients undergoing hemodialysis. This research method uses exploratory descriptive research with cross-sectional design. The population is all patients undergoing hemodialysis therapy. A sample of 63 clients was recruited by purposive sampling technique, the criteria were Undergoing hemodialysis therapy 2x/week and aged between 18-55 years. Variables are nutritional status (Subjects Global Assessment/ SGA and Body Mass Index/ BMI) and quality of life as measured by a modified questionnaire from previous studies. Data analysis was carried out using Logistic Regression and Spearman's rho with a degree of significance p < 0.05. The results showed that nutritional status was not related to the quality of life of chronic kidney disease patients undergoing hemodialysis (0.988 and 0.952). Follow-up analysis found that BMI and SGA had a significant relationship with the burden of kidney disease and role- physics, which are indicators of quality of life. Nutritional status is not related to the quality of life, and remains an important factor to improve health. Future research needs to look at the biomolecular of nutritional status and its relation to health.